2022
DOI: 10.1093/jee/toac007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Constant Temperatures on Life History and Life Table Parameters of Trichogramma euproctidis (Hymenoptera: Trichogrammatidae)

Abstract: Temperature has a profound effect on performance and behavior of egg parasitoids. Egg parasitoids are a well-known alternative for the control of lepidopterous pests. Selected life history parameters of Trichogramma euproctidis (Girault) (Hymenoptera: Trichogrammatidae), an established egg parasitoid species in Khuzestan- Southwest Iran, were appraised at eight constant temperatures (22.5, 25, 27.5, 30, 32.5, 35, 37.5, and 40°C) using Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs as the host. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
3
4
1
Order By: Relevance
“…Trichogramma species are known to prefer young host eggs (Hou et al 2018, Tabebordbar et al 2022b) and parasitize significantly fewer eggs with increasing host age (Myint et al 2022), as was shown in T. pintoi parasitizing H. vitessoides eggs of different ages in our study. We noted no significant differences in the T. pintoi emergence rate and percentage of F1 females among H. vitessoides eggs of different ages in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Trichogramma species are known to prefer young host eggs (Hou et al 2018, Tabebordbar et al 2022b) and parasitize significantly fewer eggs with increasing host age (Myint et al 2022), as was shown in T. pintoi parasitizing H. vitessoides eggs of different ages in our study. We noted no significant differences in the T. pintoi emergence rate and percentage of F1 females among H. vitessoides eggs of different ages in this study.…”
Section: Discussionsupporting
confidence: 81%
“…At 30−40°C, the distribution probability of S. frugiperda reached the peak. When the ambient temperature is 22.5−32.5°C, the reproductive rate of T. pretiosum is positively correlated with the temperature, and the maximum amount of eggs is laid at 32.5°C (Tabebordbar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is a crucial factor affecting insect development, fecundity behavior and fitness [ 19 , 20 ]. Insect life tables have been extensively used to analyze and understand the effects of environmental factors, including temperature, on the survival, growth, and reproduction of insects [ 21 , 22 , 23 ]. Life tables have also been widely applied in the study of insect population ecology and pest management.…”
Section: Discussionmentioning
confidence: 99%